Implementasi Payment Gateway pada Platform Freelance Digital Menggunakan Rest API - Muhammad Agung Laksono; Irwan Alnarus Kautsar; Hamzah Setiawan (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
In the continuously evolving digital era, the use of payment gateways has become a crucial element in online business transactions. A payment gateway is a technology or service that enables companies or institutions and applications to accept electronic payments or other digital payment methods. This study employs an Agile Development approach to implement a payment gateway on a digital freelance platform. Agile Development was chosen for its flexibility and iterative approach, allowing for quick adjustments to changing needs. The results indicate that the payment gateway on this freelance platform operates quite effectively. Testing on the platform showed successful outcomes with a success rate of 87%. This research demonstrates that integrating a payment gateway via REST API not only enhances the operational efficiency of the freelance platform but also strengthens user trust in the digital payment system, thereby supporting the growth and sustainability of the freelance platform's business.